Use of microcurrent as a treatment for static facial wrinkles: A bibliographic study (Research, Society and Development, 2023)
Introduction: The degradation of collagen and elastin results in the formation of wrinkles and loss of skin elasticity, characterized by a decrease in elastic fibers and collagen stiffness. Microcurrent is an approach aimed at emitting bioelectrical signals from the human body, generating electrical current to compensate for reduced bioelectricity in aged or injured cells. Objective: This literary review seeks to analyze the effects of using microcurrent on static wrinkles in the middle and upper third of the face. Methodology: The research constitutes a bibliographic review carried out through searches in databases such as LILACS, PUBMED, and GOOGLE ACADÊMICO, as well as other relevant sources. The inclusion criteria cover free articles in Portuguese, published between 2007 and November 2023, related to the topic, while the exclusion criteria include studies outside the scope or carried out on animals. Results: The literature indicates that microcurrent is more effective when applied with electrodes fixed to the skin, compared to pen-type electrodes, and when associated with other currents. Mild, moderate and severe complications were observed. Conclusion: This research highlights the need for additional studies, as there is no consensus on the effectiveness of MENS in static wrinkles. Some studies advocate the combination of MENS with other anti-aging treatments or cosmetics, while others indicate the isolated effectiveness of MENS application.